Method for testing dissolution of transition metal in positive electrode material of lithium battery
By preparing and activating the soft-packed battery core, the test positive electrode sheet was obtained and packaged into a fake battery core for high-temperature storage. Finally, through the ICP test, the problem of interference factors in the existing test method was solved and more accurate transition metal dissolution of the positive electrode material was achieved. Quantity measurement.
Patent Information
- Application Number
- CN202411537789.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-21
AI Technical Summary
There are interfering factors in the existing transition metal dissolution test methods for the positive electrode material of lithium-ion batteries, resulting in inaccurate test results, affecting the material performance characterization and judgment of failure sources.
Use a lithium battery positive material transition metal solution test method. By preparing a soft -packed battery core, activating the battery, charging to a specific SOC, disassembling the test of the positive film, injected the electrolytic solution into a fake battery cell, and the high temperature storage is performed. In the end Perform the ICP test of the electrolyte of the fake cell to obtain the amount of the transition metal of the positive material.
Reduced the interference of air oxidation and negative chips and diaphragms, improved the accuracy of the test results, and made the measurement of the amount of metal dissolved in the transition of the positive pole material more reliable.
Smart Images

Figure CN119334928A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of positive electrode material testing and analysis, and in particular to a transition metal dissolution testing method for positive electrode materials of lithium batteries. Background Art
[0002] With the continuous development of lithium-ion battery technology, its energy density, cycle stability and safety have been significantly improved. The positive electrode materials of lithium-ion batteries include lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium iron phosphate and ternary materials composed of nickel, cobalt, manganese and other elements. During the charging and discharging process of these materials, the insertion and deinsertion of lithium ions will cause slight changes in the structure of the positive electrode materials, thereby triggering the dissolution of transition metal ions.
[0003] The dissolution test of positive electrode materials is an important means to evaluate the amount of metal ions dissolved from positive electrode materials during battery cycling. The results of the dissolution test of positive electrode materials are of great significance for evaluating the stability of battery materials, characterizing material performance and developing materials. When lithium-ion batteries are directly disassembled and the electrolyte is tested, the negative electrode material may react with the metal ions in the electrolyte, resulting in the dissolution of transition metals. As an important component of the battery, the performance and structure of the diaphragm also affect the amount of transition metal dissolution from the positive electrode material, making the test results of transition metal dissolution in the electrolyte inaccurate. The positive electrode material sample is placed in a certain amount of electrolyte through an offline detection method. Stir continuously for a certain period of time to allow the positive electrode material to fully contact the electrolyte. Take out the electrolyte and perform chemical analysis. The oxidation of the electrolyte and air will interfere with the dissolution of transition metals in the positive electrode material, and cannot reflect the dissolution of transition metals when the positive electrode sheet in the battery cell is in actual contact with the electrolyte, thereby affecting the judgment and analysis of the technical personnel in the characterization of material performance and confirmation of the source of failure.
[0004] For example, the comparative document CN201910333978.2 discloses a method for judging the performance of a positive electrode material for a lithium-ion battery. Although it discloses taking a positive electrode material for a lithium-ion battery, making it into a battery, and detecting the metal dissolution on the electrode piece, its test model is exposed to the air, the electrolyte is oxidized by the air, and the dissolution of transition metals during actual contact between the positive electrode piece and the electrolyte is not fully considered, resulting in inaccurate results of the measured dissolution of transition metals, which in turn adversely affects the judgment and analysis of technical personnel in this field on characterizing material properties and confirming the source of failure. Summary of the invention
[0005] The purpose of the present disclosure is to overcome the deficiencies in the prior art and provide a method for reducing interference factors, thereby reducing adverse interference factors that may be generated by technical personnel in the contact environment between the positive electrode sheet and the electrolyte in characterizing material properties and confirming the source of failure.
[0006] The purpose of this disclosure is achieved through the following technical solutions:
[0007] A method for testing transition metal dissolution of lithium battery positive electrode materials comprises the following steps:
[0008] Preparing soft-pack batteries;
[0009] Activating the soft-pack battery cell to obtain an activated battery cell;
[0010] Charging the SOC of the activated cell to 10%-100% to obtain a test cell;
[0011] Disassembling the test cell to obtain a test positive electrode sheet;
[0012] Put the test positive electrode sheet into an aluminum plastic shell, inject electrolyte and seal it to obtain a fake battery cell;
[0013] Putting the dummy battery cell into an oven for heat storage;
[0014] The fake battery cell is disassembled, the electrolyte is taken out, and an ICP test is performed on the electrolyte to obtain the dissolution amount of the transition metal of the positive electrode material.
[0015] In one embodiment, preparing the soft-pack battery cell comprises the following steps:
[0016] Prepare a positive electrode sheet and a negative electrode sheet of a battery cell, and wind the positive electrode sheet, the negative electrode sheet and a separator to obtain a winding core;
[0017] The winding core is installed in an aluminum-plastic film and an electrolyte is injected for packaging;
[0018] The aluminum-plastic film is sealed under negative pressure to obtain a soft-pack battery cell.
[0019] In one embodiment, the electrolyte is injected for negative pressure packaging to obtain a soft-pack battery cell, and the soft-pack battery cell is activated to obtain an activated battery cell, and the following steps are also included:
[0020] The soft-pack battery cell is allowed to stand at a temperature of 20° C.-25° C. for a time of 24 h-72 h.
[0021] In one embodiment, placing the test positive electrode sheet into an aluminum-plastic shell and injecting electrolyte to encapsulate the shell comprises the following steps:
[0022] The positive electrode sheet to be tested is bent and overlapped and placed in an aluminum-plastic shell;
[0023] injecting electrolyte for packaging;
[0024] The aluminum-plastic shell is sealed with low negative pressure to obtain a fake battery cell.
[0025] In one embodiment, the temperature of the dummy battery cell placed in the oven for heat storage is 45°C-85°C.
[0026] In one embodiment, the dummy battery cell is placed in an oven for heat storage for 4 to 14 days.
[0027] In one embodiment, charging and discharging the soft-pack battery cell for activation comprises the following steps:
[0028] At a temperature of 25° C. to 60° C., charging the soft-pack battery cell at a rate of 0.05C for 0.5 h to 2 h;
[0029] Then the soft-pack battery cell is charged at a rate of 0.1C for 1h-3h;
[0030] Then, the soft-pack battery cell is fully charged at a rate of 0.2C-0.5C;
[0031] Then the soft-pack battery cell is discharged to 0% SOC at a rate of 0.1-0.5C.
[0032] In one embodiment, after charging the SOC of the soft-pack battery cell to 10%-100%, before disassembling the test battery cell, the following steps are also included:
[0033] The test cell is left to stand at a temperature of 20° C.-25° C. for a time of 1 h-10 h.
[0034] In one embodiment, performing ICP testing on the electrolyte comprises the following steps:
[0035] The electrolyte is diluted and fixed to volume using ethanol as an intermediate solvent to obtain a test solution;
[0036] The liquid to be tested is subjected to instrument detection.
[0037] In one of the embodiments, the main material of the positive electrode sheet of the battery cell is at least one of lithium manganese oxide, ternary material, lithium iron manganese phosphate, lithium iron phosphate, and lithium cobalt oxide.
[0038] Compared with the prior art, the present invention has at least the following advantages:
[0039] The above-mentioned transition metal dissolution test method for lithium battery positive electrode materials comprises the following steps: preparing a soft-pack battery cell, disassembling the soft-pack battery cell to obtain a test positive electrode sheet, injecting the test positive electrode sheet into an electrolyte to encapsulate a dummy battery cell, storing the dummy battery cell at high temperature, and then testing the electrolyte of the dummy battery cell to obtain the amount of transition metal dissolution of the positive electrode material, so that the test positive electrode sheet in the dummy battery cell is isolated from the air, thereby avoiding the interference of electrolyte oxidation factors on the amount of transition metal dissolution of the positive electrode material, and the test positive electrode sheet in the dummy battery cell is in contact with the electrolyte alone, thereby avoiding the interference of the negative electrode sheet and the diaphragm on the amount of transition metal dissolution of the positive electrode material, thereby reducing the adverse interference factors in the contact environment between the test positive electrode sheet and the electrolyte for the judgment and analysis of technical personnel in characterizing material properties and confirming the source of failure. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to more clearly illustrate the technical solutions of the embodiments of the present disclosure, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present disclosure and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0041] Figure 1 A flow chart of the steps of a method for testing transition metal dissolution of a lithium battery positive electrode material according to an embodiment;
[0042] Figure 2 It is a curve chart of the dissolution amount of transition metal Mn in Examples 1-5 and Comparative Examples 1-5. DETAILED DESCRIPTION
[0043] In order to facilitate the understanding of the present disclosure, the present disclosure will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present disclosure are given in the drawings. However, the present disclosure can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present disclosure more thoroughly and comprehensively understood.
[0044] It should be noted that when an element is referred to as being "fixed to" another element, it may be directly on the other element or there may be a central element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be a central element at the same time. The terms "vertical", "horizontal", "left", "right" and similar expressions used herein are for illustrative purposes only and do not represent the only implementation method.
[0045] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present disclosure. The terms used herein in the specification of the present disclosure are only for the purpose of describing specific embodiments and are not intended to limit the present disclosure. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0046] In order to better understand the technical solutions and beneficial effects of the present invention, the present invention is further described in detail below in conjunction with specific embodiments:
[0047] The present invention relates to a method for testing the dissolution of transition metals in positive electrode materials of lithium batteries. In one embodiment, a method for testing the dissolution of transition metals in positive electrode materials of lithium batteries comprises the following steps: preparing a soft-pack battery cell; activating the soft-pack battery cell to obtain an activated battery cell; charging the SOC of the activated battery cell to 10%-100% to obtain a test battery cell; disassembling the test battery cell to obtain a test positive electrode sheet; placing the test positive electrode sheet in an aluminum-plastic shell, injecting electrolyte to encapsulate, to obtain a dummy battery cell; placing the dummy battery cell in an oven for heat storage; disassembling the dummy battery cell, taking out the electrolyte, and performing an ICP test on the electrolyte to obtain the dissolution amount of transition metals in the positive electrode material.
[0048] See also Figure 1 , which is a transition metal dissolution test method for lithium battery positive electrode materials according to an embodiment of the present invention, comprising the following steps:
[0049] S101 prepares soft-pack batteries. In this embodiment, by preparing soft-pack batteries, the environment of the positive electrode sheet to be tested is the same as the positive electrode sheet structure in the actual produced battery cell, which is conducive to testing and analyzing the actual metal dissolution of the positive electrode sheet to be tested.
[0050] S103 activates the soft-pack battery cell to obtain an activated battery cell. In this embodiment, the soft-pack battery cell is activated by charging and discharging, so that a chemical reaction occurs inside the soft-pack battery cell to form an SEI film. During the first cycle of the soft-pack battery cell, the electrolyte and the negative electrode material react at the solid-liquid interphase layer to form a passivation film, so that the positive electrode sheet, the negative electrode sheet and the electrolyte reach a state of equilibrium, which is beneficial to the subsequent detection of the positive electrode sheet to be tested.
[0051] S105 charges the SOC of the activated cell to 10%-100% to obtain a test cell. In this embodiment, when the SOC of the cell is less than 10%, it means that the remaining power of the cell is low and close to a fully discharged state. The internal chemical reaction may become unstable, thereby affecting the transition metal dissolution result of the positive electrode material of the test positive electrode sheet. Therefore, the SOC of the activated cell needs to be charged to 10%-100% for testing. By charging the soft-pack cell to different SOCs, it is convenient to test the transition metal dissolution of the positive electrode sheet of the soft-pack cell with different SOCs.
[0052] S107 disassembles the test battery cell to obtain a test positive electrode sheet. In this embodiment, the battery disassembly needs to strictly comply with safety precautions to ensure the safety and efficiency of the battery disassembly process. During the disassembly process, the temperature and humidity of the environment need to be controlled for disassembly, and a rotary dehumidifier or other dehumidification equipment is used to control the humidity so that the humidity of the disassembly environment is below 30% RH and the temperature is controlled between 20°C-25°C to maintain the stability of the internal materials of the battery, thereby reducing safety hazards caused by temperature changes.
[0053] S109: placing the test positive electrode sheet into an aluminum-plastic shell, injecting electrolyte to encapsulate, and obtaining a dummy battery cell. In this embodiment, after the soft-pack battery cell is disassembled, the test positive electrode sheet is placed into an aluminum-plastic shell, and after injecting electrolyte to encapsulate, the air is isolated from the electrolyte, so that the test positive electrode sheet is in full contact with the electrolyte, and the influence of the negative electrode sheet and the diaphragm on the dissolution of transition metals in the electrolyte is avoided, so that the transition metal dissolution amount of the positive electrode material measured by the test positive electrode sheet is more accurate.
[0054] S111: placing the dummy battery cell in an oven for heat storage. In this embodiment, when the dummy battery cell is subjected to heat storage, the reactivity of the electrolyte and the transition metal is enhanced, so that the electrochemical reaction rate on the electrolyte interface is accelerated, thereby accelerating the dissolution rate of the transition metal of the positive electrode material of the positive electrode sheet in the dummy battery cell in the electrolyte, thereby shortening the test time of the dissolution of the transition metal of the positive electrode material of the lithium battery.
[0055] S113: dismantling the fake battery cell, taking out the electrolyte, and performing an ICP test on the electrolyte to obtain the amount of transition metal dissolved in the positive electrode material. In this embodiment, testing the amount of transition metal dissolved in the electrolyte in the fake battery cell can more accurately reflect the amount of transition metal dissolved in the positive electrode material.
[0056] The above-mentioned transition metal dissolution test method for lithium battery positive electrode materials comprises the following steps: preparing a soft-pack battery cell, disassembling the soft-pack battery cell to obtain a test positive electrode sheet, injecting the test positive electrode sheet into an electrolyte to encapsulate a dummy battery cell, storing the dummy battery cell at high temperature, and then testing the electrolyte of the dummy battery cell to obtain the amount of transition metal dissolution of the positive electrode material, so that the test positive electrode sheet in the dummy battery cell is isolated from the air, thereby avoiding the interference of electrolyte oxidation factors on the amount of transition metal dissolution of the positive electrode material, and the test positive electrode sheet in the dummy battery cell is in contact with the electrolyte alone, thereby avoiding the interference of the negative electrode sheet and the diaphragm on the amount of transition metal dissolution of the positive electrode material, thereby reducing the adverse interference factors in the contact environment between the test positive electrode sheet and the electrolyte for the judgment and analysis of technical personnel in characterizing material properties and confirming the source of failure.
[0057] In one embodiment, a positive electrode sheet and a negative electrode sheet of a battery cell are prepared, and the positive electrode sheet, the negative electrode sheet and a separator are wound to obtain a winding core;
[0058] The winding core is installed in an aluminum-plastic film and an electrolyte is injected for packaging;
[0059] The aluminum-plastic film is sealed under negative pressure to obtain a soft-pack battery cell.
[0060] In the present embodiment, the aluminum-plastic film is injected with electrolyte for packaging and capped in a negative pressure environment below atmospheric pressure, so that the gas inside the soft-pack battery cell is effectively discharged, thereby reducing the contact between the material inside the soft-pack battery cell and the oxygen in the air, preventing the internal material of the soft-pack battery cell from undergoing oxidation reaction, reducing the bubbles and voids inside the soft-pack battery cell, and improving the charge and discharge efficiency and cycle life of the soft-pack battery cell. The positive electrode sheet, negative electrode sheet and diaphragm in the soft-pack battery cell are the same as the cell structure prepared in the actual production process, so that the environment in which the positive electrode sheet of the battery cell is located is the same as that of the positive electrode sheet actually produced, thereby effectively simulating the changes in the positive electrode material of the positive electrode sheet of the battery cell.
[0061] Furthermore, when the roll core is installed in the aluminum-plastic film and the electrolyte is injected for negative pressure packaging, the pressure of the negative pressure packaging is between -1.0kPa and -0.4kPa. When the negative pressure of the negative pressure packaging of the soft-pack battery is too large, it will cause the internal structure of the battery to deform, causing the electrolyte between the electrodes to be compressed, thereby reducing the capacity of the battery, and also causing excessive internal stress in the battery, ultimately leading to battery failure. Therefore, the negative pressure packaging pressure is controlled between -1.0kPa and -0.4kPa, so that the gas inside the soft-pack battery cell is effectively discharged, reducing the bubbles and gaps inside the soft-pack battery cell, and reducing the influence of the negative pressure packaging pressure on the soft-pack battery cell, so that the obtained soft-pack battery cell structure remains stable.
[0062] Furthermore, in one of the embodiments, when preparing the positive electrode sheet and the negative electrode sheet of the battery cell, the positive electrode sheet and the negative electrode sheet of the battery cell are cut into fixed sizes by a mold. In this embodiment, the positive electrode sheet of the battery cell and the negative electrode sheet of the battery cell are accurately cut into fixed sizes and shapes by precision stamping or cutting of the mold. The alignment between the positive electrode sheet and the negative electrode sheet of the battery cell is improved, and the space waste of the positive electrode sheet, the negative electrode sheet and the diaphragm of the battery cell is reduced during winding, the stability of the internal structure of the battery cell is ensured, and the consistency of the positive electrode sheet and the negative electrode sheet of the battery cell in the battery is improved, thereby facilitating quantitative testing of soft-pack batteries.
[0063] Furthermore, the number of winding layers of the battery cell positive electrode sheet, the battery cell negative electrode sheet and the separator is 5-10 layers. It is understandable that when the number of winding layers of the battery cell positive electrode sheet, the battery cell negative electrode sheet and the separator is greater than 10, the production process may become cumbersome, increasing the difficulty of operation and production cost; when the number of winding layers of the battery cell positive electrode sheet, the battery cell negative electrode sheet and the separator is less than 5, it may affect the performance and stability of the battery; when the number of winding layers of the battery cell positive electrode sheet, the battery cell negative electrode sheet and the separator is controlled at 5-10 layers, the production process of the soft-pack battery cell is more controllable and predictable, and the appropriate number of layers can reduce the complexity and time consumption of the production process, ensure the stability of the internal structure of the battery, and the wound battery cell positive electrode sheet, battery cell negative electrode sheet and separator form a stable structure inside the battery, which helps to reduce the deformation and stress concentration of the battery during the charging and discharging process, so that the obtained soft-pack battery cell structure is stable, and testers can measure the performance parameters of the battery more accurately, thereby facilitating quantitative testing of the soft-pack battery cell.
[0064] In one embodiment, the electrolyte is injected for negative pressure packaging to obtain a soft-pack battery cell, and the soft-pack battery cell is activated to obtain an activated battery cell, and the following steps are also included:
[0065] The soft-pack battery cell is placed at room temperature, the temperature is 20° C.-25° C., and the time is 24 h-72 h.
[0066] In this embodiment, the packaged battery cell is left at room temperature of 20°C-25°C for 24h-72h, so that the electrolyte and chemical substances inside the battery cell reach a relatively stable state and the electrolyte fully infiltrates the positive electrode sheet and the negative electrode sheet of the battery cell.
[0067] In one embodiment, placing the test positive electrode sheet into an aluminum-plastic shell and injecting electrolyte to encapsulate the shell comprises the following steps:
[0068] The positive electrode sheet to be tested is bent and overlapped and placed in an aluminum-plastic shell;
[0069] injecting electrolyte for packaging;
[0070] The aluminum-plastic shell is sealed with low negative pressure to obtain a fake battery cell.
[0071] In this embodiment, the positive electrode sheet to be tested is bent and overlapped to form a plurality of positive electrode sheet layers, each of which is in contact with the electrolyte, so that the electrolyte can quickly infiltrate the positive electrode sheet to be tested. The aluminum-plastic shell is injected with electrolyte, and after low negative pressure packaging, only the electrolyte and the positive electrode sheet to be tested are retained in the aluminum-plastic shell, thereby avoiding the interference of the electrolyte and air oxidation factors on the dissolution amount of transition metals in the positive electrode material, and avoiding the interference of the negative electrode sheet and the diaphragm on the dissolution amount of transition metals in the positive electrode material.
[0072] Furthermore, in one of the embodiments, when the aluminum-plastic shell is capped with low negative pressure, the pressure of the low negative pressure package is between -0.4 kPa and 0 kPa. In the present embodiment, since there are only the test positive electrode sheet and the electrolyte in the aluminum-plastic shell, which is different from the winding core structure of the positive electrode sheet, the diaphragm and the negative electrode sheet in the soft-pack battery cell, the structure of the aluminum-plastic shell and the test positive electrode sheet is softer, and the electrolyte added to the aluminum-plastic shell is less. When the pressure is less than -0.4kPa, the electrolyte is easily extracted, so that the electrolyte content is less, which affects the contact between the electrolyte and the test positive electrode sheet, and easily causes the aluminum-plastic shell and the test positive electrode sheet to deform. When the pressure is greater than 0kPa, the air in the aluminum-plastic shell cannot be extracted during packaging, so that the electrolyte contacts and oxidizes with the air, thereby affecting the dissolution amount of transition metals of the positive electrode material of the positive electrode sheet; when the pressure of the low negative pressure packaging is between -0.4kPa and 0kPa, the air in the aluminum-plastic shell can be extracted, and the contact between the test positive electrode sheet and the electrolyte is better, and the structure of the test positive electrode sheet and the aluminum-plastic shell is stable, so that the test result of the test positive electrode sheet of the fake battery is more stable.
[0073] Furthermore, the test positive electrode sheet is bent and overlapped to form a plurality of positive electrode sheet layers, the number of the positive electrode sheet layers is 1-10, and the amount of electrolyte added to each positive electrode sheet layer is 3g-10g. In this embodiment, the contact between the test positive electrode sheet and the electrolyte in the dummy battery simulates the contact between the positive electrode sheet and the electrolyte of the battery cell actually produced. The amount of electrolyte corresponding to each layer of the positive electrode sheet ensures that the quantitative electrolyte can fully infiltrate the test positive electrode sheet. The amount of electrolyte and the test positive electrode sheet directly affects the test result of the metal dissolution amount of the positive electrode material. By quantitatively controlling the amount of electrolyte and the test positive electrode sheet, the consistency of the electrolyte and the amount of positive electrode sheet used for each test positive electrode sheet sample can be ensured, the test efficiency can be improved, and the accuracy and reliability of the test results between each test positive electrode sheet sample can be ensured.
[0074] Furthermore, in one embodiment, after the test positive electrode sheet is bent and overlapped and placed in the aluminum-plastic shell, before the electrolyte is injected for packaging, the following steps are also included:
[0075] One end of the test positive electrode sheet is reserved with an adhesive portion, and the adhesive portion of the test positive electrode sheet is fixed to the inner wall of the aluminum-plastic shell with an adhesive tape. In this embodiment, the adhesive portion of the test positive electrode sheet covered by the adhesive tape does not contact the electrolyte, and the adhesive portion of the test positive electrode sheet is away from the side of the aluminum-plastic shell for low negative pressure capping. The test positive electrode sheet is fixed inside the aluminum-plastic shell by the adhesive tape, which avoids the movement of the test positive electrode sheet and facilitates the operation of low negative pressure capping after the aluminum-plastic shell is injected with electrolyte; after the fake battery cell is prepared, it is necessary to move the fake battery cell for hot storage, and the test positive electrode sheet is fixed inside the aluminum-plastic shell, which avoids the test positive electrode sheet from shaking, thereby affecting the change in the contact area between the test positive electrode sheet and the electrolyte, so that the test result of the test positive electrode sheet of the fake battery cell is more stable.
[0076] In one of the embodiments, the temperature at which the fake battery cell is placed in the oven for heat storage is 45°C-85°C. In this embodiment, when the temperature at which the fake battery cell is placed in the oven for static storage is greater than 45°C, the dissolution rate of the positive electrode material and the electrolyte in the fake battery cell is accelerated, thereby saving test time. When the temperature of the fake battery cell exceeds 85°C, the electrolyte inside the battery may begin to decompose, generating a large amount of heat and gas. At the same time, the thermal stability of the positive electrode material decreases, thereby affecting the dissolution amount of the positive electrode material transition metal in the electrolyte. When the temperature of the fake battery cell is placed in the oven at 45°C-85°C, the dissolution rate of the positive electrode material transition metal and the electrolyte of the test positive electrode sheet of the fake battery cell is faster, and the electrolyte and the positive electrode material are stable, thereby shortening the test storage time of the fake battery cell and obtaining accurate test results of the dissolution amount of the positive electrode material transition metal of the positive electrode sheet.
[0077] In one of the embodiments, the fake battery cell is placed in an oven for hot storage for 4 to 14 days. In this embodiment, after the fake battery cell is left to stand, the chemical substances inside the battery cell can be more evenly distributed, so that the electrolyte fully penetrates into the positive electrode material of the positive electrode sheet, so that the transition metal of the positive electrode material dissolves into the electrolyte. When the static storage time is less than 4 days, the transition metal dissolution of the positive electrode material is not complete, so that the measured transition metal dissolution amount is too low. When the static storage time in the oven is greater than 14 days, the chemical reaction inside the battery cell may change, such as the decomposition of the electrolyte, the oxidation of the electrode material, etc., thereby affecting the accuracy of the battery cell test.
[0078] In one embodiment, charging and discharging the soft-pack battery cell for activation comprises the following steps:
[0079] At a temperature of 25° C. to 60° C., charging the soft-pack battery cell at a rate of 0.05C for 0.5 h to 2 h;
[0080] The soft-pack battery cell is charged at a rate of 0.1C for 1 h to 3 h;
[0081] Fully charging the soft-pack battery cell at a rate of 0.2C-0.5C;
[0082] The soft-pack battery cell is discharged to 0% SOC at a rate of 0.1-0.5C. In this embodiment, the initial low-rate charging helps the active material and electrolyte inside the battery cell to make initial contact and start a chemical reaction. By gradually increasing the charging rate, the chemical reaction rate inside the battery cell is accelerated, the contact between the active material and the electrolyte is more complete, and the battery cell is further activated. The high-rate full charge ensures that the battery cell obtains sufficient electricity in a short time. Through charge and discharge activation, the active material and the electrolyte inside the soft-pack battery cell are fully in contact and react, so that the positive electrode sheet, the negative electrode sheet and the electrolyte of the soft-pack battery cell reach a state of equilibrium, ensuring the stability of the positive electrode sheet of the soft-pack battery cell in subsequent tests.
[0083] In one embodiment, after charging the SOC of the soft-pack battery cell to 10%-100%, before disassembling the test battery cell, the following steps are also included:
[0084] The test cell is allowed to stand at a temperature of 20°C-25°C and a standing time of 1h-10h. In this embodiment, too high a temperature may accelerate the chemical reaction inside the cell, resulting in a decrease in performance; while too low a temperature may affect the charge distribution and chemical reaction rate inside the cell. Therefore, in order to keep the test cell in a stable state before disassembly, the test cell is placed in a constant temperature room at a room temperature of 20°C-25°C for standing. It is understandable that after charging is completed, there may be certain chemical reactions and uneven charge distribution inside the cell. By standing, the chemical reaction inside the cell can gradually stabilize, and the charge distribution can be more uniform, thereby improving the performance and safety of the cell. The cell state after standing is more stable, which is conducive to the subsequent testing or use of the soft-pack cell.
[0085] In one embodiment, performing ICP testing on the electrolyte comprises the following steps:
[0086] The electrolyte is diluted and fixed to volume using ethanol as an intermediate solvent to obtain a test solution;
[0087] The liquid to be tested is subjected to instrument detection. In the present embodiment, ethanol has good solubility, which helps to evenly dilute the components in the electrolyte and reduce interference during the test. The diluted electrolyte is transferred to a volumetric flask, and the volume is adjusted to the scale line with ethanol to obtain the liquid to be tested. During the volume adjustment process, attention should be paid to shaking to ensure that the electrolyte is evenly distributed in the volumetric flask, and the treated liquid to be tested is introduced into the ICP spectrometer through the injection system. In the ICP spectrometer, high-frequency induction heating excites the atoms or ions in the sample to emit light. By detecting the wavelength and intensity of these lights, the content of various components in the electrolyte can be determined. It is understandable that after the battery liquid is poured out from the fake battery core, it is directly placed in the ICP spectrometer for detection after being diluted and adjusted to volume with ethanol. The electrolyte treatment steps are relatively few, which reduces the influence of the external environment on the electrolyte, thereby making the liquid to be tested and the result of the measured amount of transition metal dissolution of the positive electrode material more accurate.
[0088] In one of the embodiments, the main material of the positive electrode sheet is at least one of lithium manganese oxide, ternary materials, lithium iron manganese phosphate, lithium iron phosphate, and lithium cobalt oxide. In this embodiment, the positive electrode sheet is an important component of the lithium battery, and the selection of its main material has a crucial impact on the performance of the lithium battery. Lithium manganese oxide, ternary materials, lithium iron manganese phosphate, lithium iron phosphate, lithium cobalt oxide and other materials each have their own unique properties and characteristics. By testing the positive electrode sheets of different main materials, the dissolution of transition metals can be well analyzed under the same test conditions between the same material or different materials, and the material performance can be more effectively characterized and the source of failure can be confirmed.
[0089] Compared with the prior art, the present invention has at least the following advantages:
[0090] The above-mentioned transition metal dissolution test method for lithium battery positive electrode materials comprises the following steps: preparing a soft-pack battery cell, disassembling the soft-pack battery cell to obtain a test positive electrode sheet, injecting the test positive electrode sheet into an electrolyte to encapsulate a dummy battery cell, storing the dummy battery cell at high temperature, and then testing the electrolyte of the dummy battery cell to obtain the amount of transition metal dissolution of the positive electrode material, so that the test positive electrode sheet in the dummy battery cell is isolated from the air, thereby avoiding the interference of electrolyte oxidation factors on the amount of transition metal dissolution of the positive electrode material, and the test positive electrode sheet in the dummy battery cell is in contact with the electrolyte alone, thereby avoiding the interference of the negative electrode sheet and the diaphragm on the amount of transition metal dissolution of the positive electrode material, thereby reducing the adverse interference factors in the contact environment between the test positive electrode sheet and the electrolyte for the judgment and analysis of technical personnel in characterizing material properties and confirming the source of failure.
[0091] Some specific examples are listed below, and if % is mentioned, it means percentage by weight. It should be noted that the following examples do not exhaust all possible situations, and the materials used in the following examples can be obtained from commercial sources unless otherwise specified.
[0092] Example 1
[0093] The main material of the positive electrode sheet is ternary NCM523 + lithium manganese oxide = 5:5, and the positive and negative electrode sheets are cut into fixed sizes according to the mold; the diaphragm is wound into 8 layers (i.e. 9 negative electrodes and 8 positive electrodes) in the form of negative electrode sheet-positive electrode sheet-negative electrode sheet, and then wound into a core.
[0094] The wound core was packaged with aluminum plastic film and injected with electrolyte. The top seal was performed under negative pressure (-0.7Kpa) to obtain a soft-pack battery cell. After the soft-pack battery cell was left at room temperature for 36 hours, the battery cell was activated at a temperature of 45°C, charged at a rate of 0.05C for 1 hour, charged at a rate of 0.1C for 1.5 hours, fully charged at a rate of 0.33C, and discharged at a rate of 0.33C to 0% SOC to obtain an activated battery cell. Then, the activated battery cell was charged at 0.33C to the required 10% SOC to obtain a test battery cell. After charging, it was left at room temperature for 5 hours.
[0095] The 10% SOC test battery cell was disassembled, leaving the positive electrode sheet. The middle part of the positive electrode sheet was selected as the test positive electrode sheet. The test positive electrode sheet was bent and overlapped in 6 layers and placed in the prepared aluminum-plastic shell. Fresh electrolyte was injected and then packaged. The electrolyte injection amount was controlled at 1 piece corresponding to 5 grams of electrolyte. The aluminum-plastic film top was packaged under a low negative pressure of -0.4Kpa to obtain a fake battery cell. The packaged fake battery cell was placed flat in a high temperature box at 60℃ and left to stand for 10 days.
[0096] After the high-temperature static test, the fake battery cell is taken out, the electrolyte is poured out after the fake battery cell is disassembled, and a certain amount of electrolyte is taken for ICP test. The ICP test result is the dissolution of transition metals in each material.
[0097] Example 2
[0098] The main material of the positive electrode sheet is ternary NCM523 + lithium manganese oxide = 5:5, and the positive and negative electrode sheets are cut into fixed sizes according to the mold; the diaphragm is wound into 8 layers (i.e. 9 negative electrodes and 8 positive electrodes) in the form of negative electrode sheet-positive electrode sheet-negative electrode sheet, and then wound into a core.
[0099] The wound core was packaged with aluminum plastic film and injected with electrolyte. The top seal was performed under negative pressure (-0.7Kpa) to obtain a soft-pack battery cell. After the soft-pack battery cell was left at room temperature for 36 hours, the battery cell was activated at a temperature of 45°C, charged at a rate of 0.05C for 1 hour, charged at a rate of 0.1C for 1.5 hours, fully charged at a rate of 0.33C, and discharged at a rate of 0.33C to 0% SOC to obtain an activated battery cell. Then, the activated battery cell was charged at 0.33C to the required 30% SOC to obtain a test battery cell. After charging, it was left at room temperature for 5 hours.
[0100] The 30% SOC test battery cell was disassembled, leaving the positive electrode sheet. The middle part of the positive electrode sheet was selected as the test positive electrode sheet. The test positive electrode sheet was bent and overlapped in 6 layers and placed in the prepared aluminum-plastic shell. Fresh electrolyte was injected and then packaged. The electrolyte injection amount was controlled at 1 piece corresponding to 5 grams of electrolyte. The aluminum-plastic film top was packaged under a low negative pressure of -0.4Kpa to obtain a fake battery cell. The packaged fake battery cell was placed flat in a high temperature box at 60℃ and left to stand for 10 days.
[0101] After the high-temperature static test, the fake battery cell is taken out, the electrolyte is poured out after the fake battery cell is disassembled, and a certain amount of electrolyte is taken for ICP test. The ICP test result is the dissolution of transition metals in each material.
[0102] Example 3
[0103] The main material of the positive electrode sheet is ternary NCM523 + lithium manganese oxide = 5:5, and the positive and negative electrode sheets are cut into fixed sizes according to the mold; the diaphragm is wound into 8 layers (i.e. 9 negative electrodes and 8 positive electrodes) in the form of negative electrode sheet-positive electrode sheet-negative electrode sheet, and then wound into a core.
[0104] The wound core was packaged with aluminum plastic film and injected with electrolyte. The top seal was performed under negative pressure (-0.7Kpa) to obtain a soft-pack battery cell. After the soft-pack battery cell was left at room temperature for 36 hours, the battery cell was activated at a temperature of 45°C, charged at a rate of 0.05C for 1 hour, charged at a rate of 0.1C for 1.5 hours, fully charged at a rate of 0.33C, and discharged at a rate of 0.33C to 0% SOC to obtain an activated battery cell. Then, the activated battery cell was charged at 0.33C to the required 50% SOC to obtain a test battery cell. After charging, it was left at room temperature for 5 hours.
[0105] The 50% SOC test battery cell was disassembled, leaving the positive electrode sheet. The middle part of the positive electrode sheet was selected as the test positive electrode sheet. The test positive electrode sheet was bent and overlapped in 6 layers and placed in the prepared aluminum-plastic shell. Fresh electrolyte was injected and then packaged. The electrolyte injection amount was controlled at 1 piece corresponding to 5 grams of electrolyte. The aluminum-plastic film top was packaged under a low negative pressure of -0.4Kpa to obtain a fake battery cell. The packaged fake battery cell was placed flat in a high temperature box at 60℃ and left to stand for 10 days.
[0106] After the high-temperature static test, the fake battery cell is taken out, the electrolyte is poured out after the fake battery cell is disassembled, and a certain amount of electrolyte is taken for ICP test. The ICP test result is the dissolution of transition metals in each material.
[0107] Example 4
[0108] The main material of the positive electrode sheet is ternary NCM523 + lithium manganese oxide = 5:5, and the positive and negative electrode sheets are cut into fixed sizes according to the mold; the diaphragm is wound into 8 layers (i.e. 9 negative electrodes and 8 positive electrodes) in the form of negative electrode sheet-positive electrode sheet-negative electrode sheet, and then wound into a core.
[0109] The wound core was packaged with aluminum plastic film and injected with electrolyte. The top seal was performed under negative pressure (-0.7Kpa) to obtain a soft-pack battery cell. After the soft-pack battery cell was left at room temperature for 36 hours, the battery cell was activated at a temperature of 45°C, charged at a rate of 0.05C for 1 hour, charged at a rate of 0.1C for 1.5 hours, fully charged at a rate of 0.33C, and discharged at a rate of 0.33C to 0% SOC to obtain an activated battery cell. Then, the activated battery cell was charged at 0.33C to the required 70% SOC to obtain a test battery cell. After charging, it was left at room temperature for 5 hours.
[0110] The 70% SOC test battery cell was disassembled, leaving the positive electrode sheet. The middle part of the positive electrode sheet was selected as the test positive electrode sheet. The test positive electrode sheet was bent and overlapped in 6 layers and placed in the prepared aluminum-plastic shell. Fresh electrolyte was injected and then packaged. The electrolyte injection amount was controlled at 1 piece corresponding to 5 grams of electrolyte. The aluminum-plastic film top was packaged under a low negative pressure of -0.4Kpa to obtain a fake battery cell. The packaged fake battery cell was placed flat in a high temperature box at 60℃ and left to stand for 10 days.
[0111] After the high-temperature static test, the fake battery cell is taken out, the electrolyte is poured out after the fake battery cell is disassembled, and a certain amount of electrolyte is taken for ICP test. The ICP test result is the dissolution of transition metals in each material.
[0112] Example 5
[0113] The main material of the positive electrode sheet is ternary NCM523 + lithium manganese oxide = 5:5, and the positive and negative electrode sheets are cut into fixed sizes according to the mold; the diaphragm is wound into 8 layers (i.e. 9 negative electrodes and 8 positive electrodes) in the form of negative electrode sheet-positive electrode sheet-negative electrode sheet, and then wound into a core.
[0114] The wound core was packaged with aluminum plastic film and injected with electrolyte. The top seal was performed under negative pressure (-0.7Kpa) to obtain a soft-pack battery cell. After the soft-pack battery cell was left at room temperature for 36 hours, the battery cell was activated at a temperature of 45°C, charged at a rate of 0.05C for 1 hour, charged at a rate of 0.1C for 1.5 hours, fully charged at a rate of 0.33C, and discharged at a rate of 0.33C to 0% SOC to obtain an activated battery cell. Then, the activated battery cell was charged at 0.33C to the required 90% SOC to obtain a test battery cell. After charging, it was left at room temperature for 5 hours.
[0115] The 90% SOC test battery cell was disassembled, leaving the positive electrode sheet. The middle part of the positive electrode sheet was selected as the test positive electrode sheet. The test positive electrode sheet was bent and overlapped in 6 layers and placed in the prepared aluminum-plastic shell. Fresh electrolyte was injected and then packaged. The electrolyte injection amount was controlled at 1 piece corresponding to 5 grams of electrolyte. The aluminum-plastic film top was packaged under a low negative pressure of -0.4Kpa to obtain a fake battery cell. The packaged fake battery cell was placed flat in a high temperature box at 60℃ and left to stand for 10 days.
[0116] After the high-temperature static test, the fake battery cell is taken out, the electrolyte is poured out after the fake battery cell is disassembled, and a certain amount of electrolyte is taken for ICP test. The ICP test result is the dissolution of transition metals in each material.
[0117] Comparative Example 1
[0118] The main material of the positive electrode sheet is ternary NCM523 + lithium manganese oxide = 5:5; the positive and negative electrode sheets are cut into fixed sizes according to the mold; the diaphragm is wound into 8 layers (i.e. 9 negative electrodes and 8 positive electrodes) in the form of negative electrode sheet-positive electrode sheet-negative electrode sheet, and then wound into a core.
[0119] The wound core was packaged with aluminum plastic film and injected with electrolyte. The top seal was performed under negative pressure (-0.7Kpa) to obtain a soft-pack battery cell. After the soft-pack battery cell was left at room temperature for 36 hours, the battery cell was activated at a temperature of 45°C, charged at a rate of 0.05C for 1 hour, charged at a rate of 0.1C for 1.5 hours, fully charged at a rate of 0.33C, and discharged at a rate of 0.33C to 0% SOC to obtain an activated battery cell. Then, the activated battery cell was charged at 0.33C to the required 10% SOC to obtain a test battery cell. After charging, it was left at room temperature for 5 hours.
[0120] The test cell battery with 10% SOC was placed flat in a high temperature box at 60°C for 10 days.
[0121] Take out the test cell after high-temperature standing, disassemble it and pour out the electrolyte, and take a certain amount of electrolyte for ICP test.
[0122] Comparative Example 2
[0123] The main material of the positive electrode sheet is ternary NCM523 + lithium manganese oxide = 5:5; the positive and negative electrode sheets are cut into fixed sizes according to the mold; the diaphragm is wound into 8 layers (i.e. 9 negative electrodes and 8 positive electrodes) in the form of negative electrode sheet-positive electrode sheet-negative electrode sheet, and then wound into a core.
[0124] The wound core was packaged with aluminum plastic film and injected with electrolyte. The top seal was performed under negative pressure (-0.7Kpa) to obtain a soft-pack battery cell. After the soft-pack battery cell was left at room temperature for 36 hours, the battery cell was activated at a temperature of 45°C, charged at a rate of 0.05C for 1 hour, charged at a rate of 0.1C for 1.5 hours, fully charged at a rate of 0.33C, and discharged at a rate of 0.33C to 0% SOC to obtain an activated battery cell. Then, the activated battery cell was charged at 0.33C to the required 30% SOC to obtain a test battery cell. After charging, it was left at room temperature for 5 hours.
[0125] The test cell battery with 30% SOC was placed flat in a high temperature box at 60°C for 10 days.
[0126] Take out the test cell after high-temperature standing, disassemble it and pour out the electrolyte, and take a certain amount of electrolyte for ICP test.
[0127] Comparative Example 3
[0128] The main material of the positive electrode sheet is ternary NCM523 + lithium manganese oxide = 5:5; the positive and negative electrode sheets are cut into fixed sizes according to the mold; the diaphragm is wound into 8 layers (i.e. 9 negative electrodes and 8 positive electrodes) in the form of negative electrode sheet-positive electrode sheet-negative electrode sheet, and then wound into a core.
[0129] The wound core was packaged with aluminum plastic film and injected with electrolyte. The top seal was performed under negative pressure (-0.7Kpa) to obtain a soft-pack battery cell. After the soft-pack battery cell was left at room temperature for 36 hours, the battery cell was activated at a temperature of 45°C, charged at a rate of 0.05C for 1 hour, charged at a rate of 0.1C for 1.5 hours, fully charged at a rate of 0.33C, and discharged at a rate of 0.33C to 0% SOC to obtain an activated battery cell. Then, the activated battery cell was charged at 0.33C to the required 50% SOC to obtain a test battery cell. After charging, it was left at room temperature for 5 hours.
[0130] The test cell battery with 50% SOC was placed flat in a high temperature box at 60°C for 10 days.
[0131] Take out the test cell after high-temperature standing, disassemble it and pour out the electrolyte, and take a certain amount of electrolyte for ICP test.
[0132] Comparative Example 4
[0133] The main material of the positive electrode sheet is ternary NCM523 + lithium manganese oxide = 5:5; the positive and negative electrode sheets are cut into fixed sizes according to the mold; the diaphragm is wound into 8 layers (i.e. 9 negative electrodes and 8 positive electrodes) in the form of negative electrode sheet-positive electrode sheet-negative electrode sheet, and then wound into a core.
[0134] The wound core was packaged with aluminum plastic film and injected with electrolyte. The top seal was performed under negative pressure (-0.7Kpa) to obtain a soft-pack battery cell. After the soft-pack battery cell was left at room temperature for 36 hours, the battery cell was activated at a temperature of 45°C, charged at a rate of 0.05C for 1 hour, charged at a rate of 0.1C for 1.5 hours, fully charged at a rate of 0.33C, and discharged at a rate of 0.33C to 0% SOC to obtain an activated battery cell. Then, the activated battery cell was charged at 0.33C to the required 70% SOC to obtain a test battery cell. After charging, it was left at room temperature for 5 hours.
[0135] The test cell battery with 70% SOC was placed flat in a high temperature box at 60°C for 10 days.
[0136] Take out the test cell after high-temperature standing, disassemble it and pour out the electrolyte, and take a certain amount of electrolyte for ICP test.
[0137] Comparative Example 5
[0138] The main material of the positive electrode sheet is ternary NCM523 + lithium manganese oxide = 5:5; the positive and negative electrode sheets are cut into fixed sizes according to the mold; the diaphragm is wound into 8 layers (i.e. 9 negative electrodes and 8 positive electrodes) in the form of negative electrode sheet-positive electrode sheet-negative electrode sheet, and then wound into a core.
[0139] The wound core was packaged with aluminum plastic film and injected with electrolyte. The top seal was performed under negative pressure (-0.7Kpa) to obtain a soft-pack battery cell. After the soft-pack battery cell was left at room temperature for 36 hours, the battery cell was activated at a temperature of 45°C, charged at a rate of 0.05C for 1 hour, charged at a rate of 0.1C for 1.5 hours, fully charged at a rate of 0.33C, and discharged at a rate of 0.33C to 0% SOC to obtain an activated battery cell. Then, the activated battery cell was charged at 0.33C to the required 90% SOC to obtain a test battery cell. After charging, it was left at room temperature for 5 hours.
[0140] The test cell battery with 90% SOC was placed flat in a high temperature box at 60°C for 10 days.
[0141] Take out the test cell after high-temperature standing, disassemble it and pour out the electrolyte, and take a certain amount of electrolyte for ICP test.
[0142] Table 1 Transition metal dissolution test table of Examples 1-5 and Comparative Examples 1-5
[0143]
[0144] As can be seen from the above table, the dissolution amounts of transition metals Ni, Co, and Mn measured in Comparative Examples 1-5 are higher than those measured in Examples 1-5. Due to the interference of the negative electrode sheet and the separator on the dissolution amount of transition metals of the positive electrode material, the dissolution amounts of transition metals Ni, Co, and Mn measured in Comparative Examples 1-5 are relatively large, and the obtained data cannot correctly reflect the actual dissolution amount of transition metals of the positive electrode sheet.
[0145] Furthermore, from the above table and Figure 2 It can be seen that in Examples 1-5, at 30% to 40% SOC, the amount of Mn dissolved shows a decreasing trend, and in Comparative Examples 1-5, at 30% to 40% SOC, the amount of Mn dissolved shows a linear trend.
[0146] When the SOC of lithium manganate is 30% to 40%, Mn3+ undergoes the Jan-Taylor effect to disproportionately generate Mn2+ and Mn4+, and more Mn2+ manganese is dissolved; the higher the SOC, the less Mn3+ content, and the less Mn is dissolved. Therefore, the Mn dissolution data in Examples 1-5 are more composite curves of when lithium manganate is 30% to 40% SOC, Mn3+ undergoes the Jan-Taylor effect to disproportionately generate Mn2+ and Mn4+. Therefore, the dissolution amounts of transition metals Ni, Co, and Mn measured in Examples 1-5 are more accurate.
[0147] The above-mentioned embodiments only express several implementation methods of the present disclosure, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the disclosed patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present disclosure, and these all belong to the protection scope of the present disclosure. Therefore, the protection scope of the disclosed patent shall be subject to the attached claims.
Claims
1. A method for testing the dissolution of transition metals from positive electrode materials of lithium batteries, characterized in that: The steps include: Preparing soft-pack batteries; Activating the soft-pack battery cell to obtain an activated battery cell; Charging the SOC of the activated cell to 10%-100% to obtain a test cell; Disassembling the test cell to obtain a test positive electrode sheet; Put the test positive electrode sheet into an aluminum plastic shell, inject electrolyte and seal it to obtain a fake battery cell; Putting the dummy battery cell into an oven for heat storage; The fake battery cell is disassembled, the electrolyte is taken out, and an ICP test is performed on the electrolyte to obtain the dissolution amount of the transition metal of the positive electrode material.
2. The lithium battery positive electrode material transition metal dissolution test method according to claim 1, characterized in that: The preparation of the soft-pack battery cell comprises the following steps: Prepare a positive electrode sheet and a negative electrode sheet of a battery cell, and wind the positive electrode sheet, the negative electrode sheet and a separator to obtain a winding core; The winding core is installed in an aluminum-plastic film and an electrolyte is injected for packaging; The aluminum-plastic film is sealed under negative pressure to obtain a soft-pack battery cell.
3. The method for testing transition metal dissolution of lithium battery positive electrode materials according to claim 2, characterized in that: The electrolyte is injected for negative pressure packaging to obtain a soft-pack battery cell, and the soft-pack battery cell is activated to obtain an activated battery cell, and the following steps are also included: The soft-pack battery cell is allowed to stand at a temperature of 20° C.-25° C. for a time of 24 h-72 h.
4. The method for testing transition metal dissolution of lithium battery positive electrode materials according to claim 1, characterized in that: Placing the test positive electrode sheet into an aluminum-plastic shell and injecting electrolyte for packaging comprises the following steps: The positive electrode sheet to be tested is bent and overlapped and placed in an aluminum-plastic shell; injecting electrolyte for packaging; The aluminum-plastic shell is sealed with low negative pressure to obtain a fake battery cell.
5. The lithium battery positive electrode material transition metal dissolution test method according to claim 1, characterized in that: The temperature of the dummy battery cell placed in the oven for heat storage is 45°C-85°C.
6. The method for testing transition metal dissolution of lithium battery positive electrode materials according to claim 1, characterized in that: The dummy battery cells are placed in an oven for heat storage for 4 to 14 days.
7. The method for testing transition metal dissolution of lithium battery positive electrode materials according to claim 1, characterized in that: The soft-pack battery cell is activated by charging and discharging cycles, comprising the following steps: At a temperature of 25° C. to 60° C., charging the soft-pack battery cell at a rate of 0.05C for 0.5 h to 2 h; Then the soft-pack battery cell is charged at a rate of 0.1C for 1h-3h; Then, the soft-pack battery cell is fully charged at a rate of 0.2C-0.5C; Then the soft-pack battery cell is discharged to 0% SOC at a rate of 0.1-0.5C.
8. The method for testing transition metal dissolution of lithium battery positive electrode materials according to claim 1, characterized in that: After the SOC of the soft pack battery cell is charged to 10%-100%, the following steps are also included before the test battery cell is disassembled: The test cell is left to stand at a temperature of 20° C.-25° C. for a time of 1 h-10 h.
9. The method for testing transition metal dissolution of lithium battery positive electrode materials according to claim 1, characterized in that: The ICP test of the electrolyte comprises the following steps: The electrolyte is diluted and fixed to volume using ethanol as an intermediate solvent to obtain a test solution; The liquid to be tested is subjected to instrument detection.
10. The method for testing transition metal dissolution of lithium battery positive electrode materials according to claim 1, characterized in that: The main material of the positive electrode sheet of the battery cell is at least one of lithium manganese oxide, ternary material, lithium iron manganese phosphate, lithium iron phosphate, and lithium cobalt oxide.
Citation Information
Patent Citations
Method for determining performance of cathode material for lithium ion battery
CN110108698A
Winding lithium ion battery and fabrication method thereof
CN103035954A
Method for evaluating stability of positive material
CN104730065A
Method for rapid evaluation of stability of cathode material for lithium ion battery
CN107565098A
Electrolyte and secondary battery
CN109786809A
Cited By
Method for judging optimal aging time and infiltration degree of manganese-based battery cell
CN120490060A
Optimal aging time and methods for determining the degree of wetting in manganese-based battery cells
CN120490060B